2020
DOI: 10.1371/journal.pone.0236005
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the influence of cerebellum on the neuroplastic modulation of intracortical motor circuits

Abstract: The cerebellum (CB) has extensive connections with both cortical and subcortical areas of the brain, and is known to strongly influence function in areas it projects to. In particular, research using non-invasive brain stimulation (NIBS) has shown that CB projections to primary motor cortex (M1) are likely important for facilitating the learning of new motor skills, and that this process may involve modulation of late indirect (I) wave inputs in M1. However, the nature of this relationship remains unclear, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…However, in our study, subjects were required to open their eyes while standing on a single leg to maintain balance, which may account for the lack of significant differences in the data. We already know that these inter-connections between cerebellum and cerebral tissue are mainly bundles of white matter fibers with the following connective pathways: the corticoponto-cerebellar pathway and cerebello-thalamo-cortical (CTC) pathway (Iwata and Ugawa, 2005;Opie and Semmler, 2020). These neural pathways are functionally involved in motor coordination and cognitive functions (Bonnì et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, subjects were required to open their eyes while standing on a single leg to maintain balance, which may account for the lack of significant differences in the data. We already know that these inter-connections between cerebellum and cerebral tissue are mainly bundles of white matter fibers with the following connective pathways: the corticoponto-cerebellar pathway and cerebello-thalamo-cortical (CTC) pathway (Iwata and Ugawa, 2005;Opie and Semmler, 2020). These neural pathways are functionally involved in motor coordination and cognitive functions (Bonnì et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These assessments indicated that the residuals were non-normal and positively-skewed. As the statistical analysis methods proposed within the protocol for this study [ 40 ] assume a normal distribution, we attempted to meet this assumption by applying log transformation. However, this failed to adequately adjust the data, and it was therefore necessary to identify an alternative test.…”
Section: Methodsmentioning
confidence: 99%
“…However, additional research is necessary to assess if and to what extent these results would be observed following only 6 h of immobilization. The effects of immobilization on other brain regions in the sensorimotor network that have been shown to influence plasticity in human M1, including premotor cortex (Huang et al, 2018 ), supplementary motor area (Hamada et al, 2009 ), and cerebellum (Opie & Semmler, 2020 ), have been less well‐studied but could also influence the targeted neurophysiologic effects observed with TMS‐based measures of M1 excitability.…”
Section: Discussionmentioning
confidence: 99%